The reaction e+e- → γγ(γ) at Z0 energies - Abreu, P; Adam, W; Adami, F; Adye, T; Akesson, T; Alekseev, G; Allen, P; Almehed, S; Alted, F; Alvsvaag, S; Amaldi, U; Anassontzis, E; et al. (1991)
The total and differential cross-sections for the reaction e+e- → γγ(γ) are measured at centre of mass energies around 91 GeV using an integrated luminosity of 4.7 pb-1. The aggreement with QED prediction is good. Consequently there is no evidence for non-standard channels which would have the same experimental signature. The lower limits on the QED cuttoff parameters are Λ+ > 113 GeV and Λ- > 95 GeV. An upper limit on the effective coupling between a possible excited electron and the gamma is derived. At 95% confidence level the branching ratios for Z0 decay into π0γ, ηψ and γγγ are below 1.5 × 10-4, 2.8 × 10-4 and 1.4 × 10-4 respectively. © 1991.